Expression of Cyp6g1 and Cyp12d1 in DDT resistant and susceptible strains of Drosophila melanogaster. - Festucci-Buselli, R.A.; Carvalho-Dias, A.S.; de Oliveira-Andrade, M.; Caixeta-Nunes, C.; Li, H.M.; Stuart, J.J.; Muir, W.; Scharf, M.E.; Pittendrigh, B.R. (Insect Molecular Biology, 2005)
The Rst(2)DDT locus (loci) in Drosophila is associated with the over-expression of two cytochrome P450 genes, Cyp6g1 and Cyp12d1. Using northern and western blot analysis we observed the expression pattern of these two genes in two DDT susceptible (Canton-S and 91-C) and three DDT resistant strains (Wisconsin, 91-R and Hikone-R). In Canton-S and 91-R, the CYP6G1 protein was constitutively expressed throughout development. In the Wisconsin strain, CYP6G1 was not expressed in third instar larvae unless the larvae are exposed to DDT. CYP12D1 protein was only expressed in adults. Cyp12d1 mRNA is induced in DDT resistant strains post-exposure to DDT and the expression patterns of Cyp12d1 mRNA varied across DDT resistant strains. Our data support the hypothesis that there is evolutionary plasticity in the expression patterns of P450s associated with metabolic pesticide resistance.